Harrier : How To Be a Fighter Pilot - Tremelling, Paul (Penguin Random House, 2022)
Paul Tremelling spent nearly twenty years with the Royal Navy's Sea Harriers, charged with standing in the way of Her Majesty's enemies. In the cockpit or crew room, the pressure was relentless, the humour merciless. It's no place for the faint-hearted. Whether landing on a pitching aircraft carrier deck in the middle of the night or screaming in to save the lives of heroes under fire in Afghanistan, there was no room for self-doubt; only honesty, confidence and do-or-die hard truth. Combining visceral action with sharp intelligence, laced with acerbic humour, Harrier pulls no punches in bringing to life the hi-octane, unforgiving world of the fighter pilot, in the air and on the ground.